Student’s Learning Journey with Generative AI: A Narrative Inquiry into the Transformation of Learning and Teaching Practices in Higher Education - Ghimire, Nawaraj; Pandey, Romkant; Thapa, Krishna Bahadur (Innovative Research Journal, 2026)
The rapidly distribution of Generative Artificial Intelligence (GenAI) tools has reconfigured the epistemic, pedagogical, and ethical scenery of higher education. While growing body of survey based and experimental research documents the prevalence and effectives of Gen AI adoption, comparatively little is known about how Information Technology (IT) teachers narratively make sense of transformation of their student’s learning journeys, particularly in resources centered higher education system. This study address gap through a qualitative narrative inquiry into the lived experience of eighteen IT teachers working in Nepalese institutions. Guided by interpretivist paradigm and informed by the conceptual lenses of five the theory and models, the study employed purposively sampling and semi structured narrative interviews to elicit teacher’s story of pedagogical change. Data interoperation was conduct using a reflective thematic analysis approach, with eight themes: learning strategies before and after AI, changes in study habits, AI as a learning companion, faculty responses to AI, teaching innovations, assessment changes, academic integrity concerns, critical thinking and creativity. Finding disclose that GenAI has enhanced, personalization, scaffolded coding and inquiry tasks and prompted a reimagining of assessment toward reliable and dialogic forms, while simultaneously raising concerns about overreliance, surface learning and the erosion of foundational competencies. This study adds to a contextual grounded, narratively ironic justification that complements dominant quantitative work and offers practical implications for instructional policy, human resource development, digital and AI enable curricula and ethical governance of GenAI in higher education.